Belief in the Utility of Cross-Partisan Empathy Reduces Partisan Animosity and Facilitates Political Persuasion. (September 2022) - Santos, Luiza A.; Voelkel, Jan G.; Willer, Robb; Zaki, Jamil
In polarized political environments, partisans tend to deploy empathy parochially, furthering division. We propose that belief in the usefulness of cross-partisan empathy—striving to understand other people with whom one disagrees politically—promotes out-group empathy and has powerful ramifications for both intra- and interpersonal processes. Across four studies (total N = 4, 748), we examined these predictions in online and college samples using surveys, social-network analysis, preregistered experiments, and natural-language processing. Believing that cross-partisan empathy is useful is associated with less partisan division and politically diverse friendship networks (Studies 1 and 2). When prompted to believe that empathy is a political resource—versus a political weakness—people become less affectively polarized (Study 3) and communicate in ways that decrease out-partisans' animosity and attitudinal polarization (Study 4). These findings demonstrate that belief in cross-partisan empathy impacts not only individuals' own attitudes and behaviors but also the attitudes of those they communicate with.